2019
DOI: 10.1111/1471-0307.12590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pasture versus indoor feeding regimes on the yield, composition, ripening and sensory characteristics of Maasdam cheese

Abstract: Maasdam cheese was manufactured from standardized milk derived from each of three feeding systems: grass (GRA), grass and clover pasture (CLO), and indoor feeding of total mixed ration (TMR). Pasture‐derived cheeses had significantly lower L* (whiteness) and higher b* values (yellowness) compared to TMR‐derived cheeses. Acetate levels were significantly lower in CLO and butyrate levels significantly higher in TMR compared to the other cheeses. Grass‐fed cheese had significantly higher scores for smooth texture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 38 publications
(112 reference statements)
1
19
0
Order By: Relevance
“…pH was affected ( p < 0.05) by RT with the highest value observed for Allevo _6. Based on the literature [20], the increase of pH in more aged samples could be the consequence of the progressive accumulation of short-chain peptides and free amino acids as well as the lower levels of lactate due to the shortage of lactose, its main fermentative substrate.…”
Section: Resultsmentioning
confidence: 99%
“…pH was affected ( p < 0.05) by RT with the highest value observed for Allevo _6. Based on the literature [20], the increase of pH in more aged samples could be the consequence of the progressive accumulation of short-chain peptides and free amino acids as well as the lower levels of lactate due to the shortage of lactose, its main fermentative substrate.…”
Section: Resultsmentioning
confidence: 99%
“…(2016) and Panthi et al. (2019) consistently observed significantly higher concentrations of total protein in milk produced from both the GRS and CLV systems when compared to the TMR system. O′Callaghan, Hennessy, et al.…”
Section: Impact Of Feeding System On Milk Compositionmentioning
confidence: 87%
“…The influence of varying dietary forage and forage:concentrate ratios on percentage milk protein has been more widely investigated in recent years (Couvreur et al., 2006; Gulati, Galvin, Lewis, et al., 2018; Harris et al., 1998; Mackle et al., 1999; McAuliffe et al., 2016; O′Callaghan, Hennessy, et al., 2016; Panthi et al., 2019). Harris et al.…”
Section: Impact Of Feeding System On Milk Compositionmentioning
confidence: 99%
“…In particular, the nature of the pasture is responsible for changes in cheese colour and aroma according to the type of forage fed to animals, as frequently reported by farmers and cheese makers. Recent studies conducted on various cheese varieties [10] have demonstrated the influence of forage preservation (e.g., grass versus hay [11], silage versus hay [12]) and the botanical composition of dry forage [13]. Other studies have been conducted to identify, quantify, and understand the effects of forage type (e.g., maize silage, hay, grass silage, pasture) [14,15].…”
Section: Introductionmentioning
confidence: 99%